The Effect of Spiritual Wellness on Men's Thoughts About Spirit Support at Birth - Çetin, Nurdilan Şener; Şolt, Ayça (Sakarya University, 2023)
Objective: This research was conducted to examine the effect of spiritual well-being on men's thoughts on spousal support at birth. Method: The research is an online survey study conducted with men in social media groups between 01.03.2022 and 05.04.2022. The type of research is descriptive, cross-sectional. The research is a descriptive, cross-sectional and online survey conducted with men in social media groups between 01.03.2022 and 05.04.2022. The universe of the research was determined as a minimum of 267 men in the research with the raosoft sample size calculation program using the unknown sample size formula. The data of the study were collected using the Personal Information Form and Spiritual Well-Being Scale. Results: The mean age of the men participating in the study was found to be 24.11+5.11 (min=19, Max=56). In the study, it was found that 61.25% of the men were married, and the average marriage period of married people was 7.35+6.25 years. In the study, it was seen that 50.5% of married men and 60.2% of single men did not receive information about birth. 82.9% of married men and 91.6% of single men stated that they wanted their spouses to prefer normal delivery. In the study, it was determined that the Spiritual Well-Being Scale scores of single men, those who received information about birth before and those who wanted to be with their spouses at birth were statistically high. Conclusion: In the study, it was seen that men with high Spiritual Well-Being levels wanted to be with their spouses more during childbirth. In this direction, it is recommended to increase the spiritual well-being of men by supporting them spiritually in order to increase the support of their spouses at birth.

Amaç: Bu araştırma erkeklerin doğumda eş desteğine yönelik düşünceleri üzerine spiritüel iyi oluşun etkisini incelemek amacıyla yapılmıştır. Yöntem: Araştırma 01.03.2022-05.04.2022 tarihleri arasında sosyal medya gruplarında yer alan erkeklerle gerçekleştirilen çevrimiçi bir anket çalışmasıdır. Araştırmanın türü tanımlayıcı, kesitseldir. Araştırmanın evreni bilinmeyen örneklem büyüklüğü formulu kullanılarak Raosoft Sample Size Calculation programı ile araştırmada minimum 267 erkek olarak belirlenmiştir. Araştırmanın verileri Kişisel Bilgi Formu ve Spritüel İyi Oluş Ölçeği kullanarak toplanmıştır. Bulgular: Araştırmaya katılan erkeklerin yaş ortalaması 24.11+5.11 (min=19, Max=56) olarak bulunmuştur. Araştırmada erkeklerin %61.25’inin evli olduğu, evlilerin ortalama evlilik süresinin 7.35+6.25 yıl olduğu bulunmuştur. Araştırmada evli erkeklerin %50.5’inin bekar erkeklerin ise %60.2’sinin doğuma ilişkin bilgi almadığı görülmüştür. Evli erkeklerin %82.9’u ve bekar erkeklerin %91.6’sı eşinin normal doğumu tercih etmesini istediğini belirtmiştir. Araştırmada bekâr erkeklerin, daha önceden doğuma yönelik bilgi alanların ve doğumda eşinin yanında olmak isteyenlerin Spritüel İyi Oluş Ölçeği puanları istatistiksel olarak önemli farklılık gösterecek şekilde yüksek olduğu saptanmıştır. Sonuç: Araştırmada erkeklerin spritüel iyi oluş düzeyleri yüksek olanların doğum esnasında eşinin yanında daha fazla olmak istedikleri görülmüştür. Bu doğrultuda doğumda eş desteğini arttırmak için erkeklerin spritüel olarak desteklenerek spiritüel iyi oluşlarının arttırılması önerilmektedir.
Erkeklerin Doğumda Eş Desteğine Yönelik Düşünceleri Üzerine Spiritüel İyi Oluşun Etkisi
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi